1969
DOI: 10.1021/jo01257a036
|View full text |Cite
|
Sign up to set email alerts
|

Plant antitumor agents. II. Structure of two new alkaloids from Camptotheca acuminata

Abstract: Further fractionation of C. acuminda has yielded two new alkaloids, hydroxycamptothecin (2) and methoxycamptothecin (3). The former could be methylated to give a methyl ether identical with 3. In order to establish the position of the hydroxyl group in ring A, MU spectra of deuterated methoxycamptothecin and of the model compounds 7-10 have been obtained. The syntheses of model compounds have been described.The isolation and structure of camptothecin 1, an alkaloid with a novel ring system exhibiting potent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…The isolation and structure proof for camptothecin and some of the analogs obtained at an early stage, 10-hydroxy and 10-methoxy camptothecin 12 enabled extensive studies to be conducted on CPT and a few of its analogs. As stated previously, CPT was remarkably active in the life prolongation of mice treated with L1210 leukemia cells, showing activity in doses between 0.5 to 4.0 mg/kg in this L1210 mouse life prolongation assay.…”
Section: G Biological Activity Of Camptothecin and Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolation and structure proof for camptothecin and some of the analogs obtained at an early stage, 10-hydroxy and 10-methoxy camptothecin 12 enabled extensive studies to be conducted on CPT and a few of its analogs. As stated previously, CPT was remarkably active in the life prolongation of mice treated with L1210 leukemia cells, showing activity in doses between 0.5 to 4.0 mg/kg in this L1210 mouse life prolongation assay.…”
Section: G Biological Activity Of Camptothecin and Analogsmentioning
confidence: 99%
“…10-Methoxy-CPT was found to be active but somewhat less active than CPT, whereas 10-hydroxy-CPT was the most active compound in the series and was more active than CPT in both L1210 and P388 leukemia life prolongation assays. [12][13][14] Unfortunately, 10-hydroxy-camptothecin is found in nature in only very small quantities, probably amounting to about 10% of the camptothecin content. All of these previous compounds were extremely insoluble in water, but it will be recalled that the lactone could be opened under mild circumstances with sodium hydroxide or sodium methoxide, and it was found that this sodium salt of CPT was very soluble in water.…”
Section: G Biological Activity Of Camptothecin and Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…10HCPT was isolated from C. acuminata (44) and BACPT was synthesized as described recently (45). The synthesis of the hydroxylterminated generation four-PGLSA dendrimer, [G4]-PGLSA-OH, was carried out as described in a previous publication (34).…”
Section: Synthesismentioning
confidence: 99%
“…1) and 10-methoxycamptothecin (MCPT, Fig. 1) [3], both possessing better activities against the cell line 9KB (human nasopharyngeal carcinoma) in vitro and P388 lymphocytic leukemia system in vivo [4]. The anticancer mechanism of CPTs is based on the inhibition of DNA replication by stabilizing cleavable complexes formed between topoisomerase I and DNA [5].…”
Section: Introductionmentioning
confidence: 99%